The Story of Prophet Yunus (AS) - Khan, Saniyasnain (Goodword Books, 2021)
This board book tells the story of Prophet Yunus (AS), emphasizing themes of patience, repentance, and trust in Allah, especially in times of hardship. It shows that no matter how deep the trouble, turning sincerely to Allah brings relief and mercy.
Prophet Yunus (AS) preached to his people, but they did not listen. He left them and was swallowed by a big fish. In the darkness, he prayed to Allah with patience and faith. Allah forgave him and saved him, teaching us to always trust and turn back to Him
Keywords: Islam